Mengatasi Kesulitan Anak dalam Pembelajaran Pecahan Menggunakan Model Konkret dan Gambar - Mutijah Mutijah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Central of curriculum development and material’s education of research and development department to state that fractions are one topics which difficult to be teached. The difficulty is seen from little of meaning of activity to be done by teachers and difficulty of accomplishment mediator of teaching as teaching aids. The result of it, teachers direct teach to making acquaintance from fraction numbers. To follow Piaget, children in primary school old are being in operational concrete stage, so followed development’s stage the children of primary school old can construct knowledge with anything can be seen and groped. Children will very difficult to accept the concept being teached abstracly. That cause, it is to be hoped the teachers in order to do teaching of fraction concept with using of teaching aids. The models can be used to teach the fraction concept followed; region model, length model, set model, and area model. The rectangle is the easiest region model for children to draw and to partition. The rectangle is the simpliest region model to teach the fraction concept In practice, teaching of fraction concept can be used region model of concrete rectangle and region model of picture rectangle. teaching of fraction, rectangle region model, concrete, picture